Beyond digital adoption: knowledge management implementation in academic libraries and its technological and organizational barriers a systematic literature review - Berliani Ardi; Muhamad Prabu Wibowo; Tamara Adriani Salim (Jurnal Konseling dan Pendidikan, 2026)
This systematic literature review examines knowledge management (KM) implementation in academic libraries by mapping technology enabled practices and identifying technological and organizational barriers that constrain adoption. Following PRISMA guided procedures, a Scopus based search (2015–2025) retrieved 118 records; after screening against predefined inclusion and exclusion criteria, 11 full-text journal articles were included for narrative synthesis. Study quality and contribution were appraised using a relevance-based scoring scheme (1–10) aligned with the review focus (technology use, implementation detail, and barrier reporting). The synthesis indicates that academic libraries operationalize KM primarily through implementation of collaborative technologies, IoT, analytics and data-driven technologies and blockchain technology and digital security systems. Key barriers recur across contexts of infrastructure limitations, limited human resource capacity, limited managerial support and policies, knowledge hoarding, and standardization and technology interoperability. Reported impacts include improved knowledge sharing, stronger service effectiveness, and enhanced support for academic activities. This review consolidates technology categories and barrier mechanisms into an implementation-oriented synthesis and offers actionable implications for library leaders and policymakers to strengthen infrastructure readiness, interoperability planning, governance clarity, and workforce capability development for sustainable KM implementation.